Student Ability To Use English Prepositions - Nuraziza Aliah; Kamsinah Kamsinah; Nurasia Natsir; Zulkaheriyah Zulkaheriyah; Sitti Jamilah (Departement of Mathematics Education, 2023)
This study aims to reveal students' understanding of prepositions and describe the types that often confuse students. Field research is the activity of collecting baseline data for research purposes. This research was conducted using tests, questionnaires, interviews, and direct observation. In this method, the author gives a test essay consisting of 30 questions. The test was given to 50 Xi SMA Hang Tuah Makassar class students to determine their understanding of English prepositions. The author proposes a questionnaire that attempts to identify the methods of language learning by students and the experience of students in learning languages. The author presents a questionnaire that attempts to identify the processes of language learning by students and the experience of students in learning languages.A preposition is a type of adjective that usually precedes its object. Prepositional properties include words expressing spatial relationships, such as y, in, on, under, over, too, from, through, etc. A noun always follows prepositions. These conjunctions show the relationship between the nouns that follow them and one of the main elements of the sentence. The noun or pronoun after the preposition is the object. The pronoun used in this position is always the object pronoun. This study showed that the average yield. of the correct answer for prepositions of place using in, on, and at can be calculated as 368/50 = 7.36. The result of using the wrong preposition is 382/50 = 7.64. These calculations show that the number of respondents who do not know how to use prepositions correctly is more excellent than those who do. Overall, this study shows that students' ability to use the prepositions in, on, and at to indicate time and place still needs to improve. But the average difference between correct and incorrect use is minimal. In other words, the results show that the ability to use prepositions in the XI SMA Hang Tuah Makassar class as respondents in this study were average.